In-situ tensile-shear test in SEM and DIC analysis of two pearlitic steel microstructures: undeformed-coarse and deformed-refined - Pablo B. Paiva Leão; João R. Barros Neto; Samuel Filgueiras Rodrigues; Ladislav Novotný; Jorge Luiz Cardoso; Luis Flavio Gaspar Herculano; Tiago Nunes Lima; Antonio J. Ramirez; Hamilton Ferreira G. de Abreu (Journal of Materials Research and Technology, 2023)
The deformation and fracture behaviors of undeformed-coarse (UC) and deformed-refined (DR) pearlitic steel microstructure were investigated via in-situ tensile-shear (TS) test in scanning electron microscopy (SEM). An original TS sample geometry was designed. Secondary Electron (SE) images were recorded in real-time and digital image correlation technique was applied to them. Due to the DR's refined microstructure, SE images, backscatter electron images, and electron backscatter diffraction techniques were additionally employed in the DR condition under an interrupted TS test. The results showed that the DR pearlitic microstructure presented a higher shear strength and absorbed energy, compared to UC, during the TS performance. UC's pearlitic microstructure experienced a high degree of microstructural deformation, while DR seemed to be highly rigid. Strain concentration was mainly observed in the UC's colony boundaries, in the DR's GBs-α, and in the DR's colony with lamellae parallel to the tensile direction. The decohesion phenomenon was observed at colony boundaries and ferrite/cementite interfaces, respectively, for UC and DR specimens. These decohesion phenomena were related to crack nucleation in both pearlitic microstructure conditions. Finally, the shear rupture occurred abruptly for UC and slowly for DR, resulting in fractures mainly comprised of a sheared flat surface and dimples, respectively.